2021
DOI: 10.3390/jcm10143149
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide for Identifying Sentinel Lymph Node in Breast Cancer after Neoadjuvant Chemotherapy: Feasibility Study

Abstract: Sentinel lymph node biopsy (SLNB) is a well-established procedure for staging clinically node-negative early breast cancer (BC). Superparamagnetic iron oxide (SPIO) demonstrated efficacy for nodal identification using a magnetic probe after local retroaeroal interstitial injection. Its benefits lie in its flexibility, which is an essential property in the global setting, where access to the isotope is difficult. To the best of our knowledge, this is the first study to evaluate the feasibility and safety of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Since AMAROS' trial results, the gold standard for SLNB in BC patients remains the RI technique, which presents a comparable detection rate to the dual technique [12,19,31]. Numerous studies confirmed the noninferiority of SPIO to RI in the upfront surgery setting [16,17,24,25,32]. Since 2014, when Rubio et al presented promising data on the outcome of SLNB after NAC using a dual tracer (SPIO-TC99) at the ASCO annual meeting [33], the results of the SENTINAC-01 clinical trial are awaited [34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since AMAROS' trial results, the gold standard for SLNB in BC patients remains the RI technique, which presents a comparable detection rate to the dual technique [12,19,31]. Numerous studies confirmed the noninferiority of SPIO to RI in the upfront surgery setting [16,17,24,25,32]. Since 2014, when Rubio et al presented promising data on the outcome of SLNB after NAC using a dual tracer (SPIO-TC99) at the ASCO annual meeting [33], the results of the SENTINAC-01 clinical trial are awaited [34].…”
Section: Discussionmentioning
confidence: 99%
“…After neoadjuvant treatment, BC patients are randomized into three groups, with SLNB guided by dual tech-nique, combined RI + SPIO or SPIO alone. Our previous study established SPIO-guided SLNB after NAC as a safe and feasible method [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations